2020
DOI: 10.1080/20426445.2020.1738118
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of modulus of elasticity ofBoscia angustifoliawood using longitudinal vibration acoustic method

Abstract: This study aimed at estimating MOE of Boscia augustifolia wood using non-destructive longitudinal vibration acoustic method with the view to examining its reliability. Three trees of B. augustifolia were obtained, and samples of 20 × 20 × 300 mm 3 were collected for dynamic and static bending testing of the wood's elasticity. The samples were stored for a month prior testing after oven dried. Mean values of dynamic (dMOE) and static modulus of elasticity (sMOE) of B. augustifolia wood obtained were 6.908 ± 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Nevertheless, a significantly higher exponential relationship between sMOE and dMOE suggests that sMOE had a suitable exponential increment with an increasing dMOE, as against the linear relationship opined by several researchers ( Leite et al 2012;Baar et al 2015;Chauhan and Sethy 2016;Olaoye and Okon-Akan 2020).…”
Section: Relationship Between Smoe and Acoustic Propertiesmentioning
confidence: 72%
“…Nevertheless, a significantly higher exponential relationship between sMOE and dMOE suggests that sMOE had a suitable exponential increment with an increasing dMOE, as against the linear relationship opined by several researchers ( Leite et al 2012;Baar et al 2015;Chauhan and Sethy 2016;Olaoye and Okon-Akan 2020).…”
Section: Relationship Between Smoe and Acoustic Propertiesmentioning
confidence: 72%
“…A reasonable reason for such variation could be attributed to a small number of data points administered (Llana & Short, 2020). Also, other authors who investigated the relationship between the standing tree acoustic measurements and the MOE of clear wood determined by longitudinal or transverse vibration methods are Chauhan and Anil (2016) and Olaoye and Okon-Akan (2020) who found R 2 of 0.98 and 0.81, respectively for clear wood samples. Also, Grabianowski et al (2006) reported a R 2 of 0.89 between MOEd determined by TOF and Resonance method with TOF method having the higher MOEd.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Acoustic technologies deployed in the measurement of material have been in existence for several decades and are widely recognized as effective non-destructive testing tools for assessing raw wood material in forest operations and wood manufacturing processes. They can be used for predicting the stiffness of standing trees, felled logs, or sawn timber (Wang et al, 2007a; Legg & Bradley, 2016) and wood samples (Chauhan & Anil 2016; Olaoye, 2019; Olaoye and Okon-Akan, 2020). Investigation into these techniques can be dated to as far back as 1935 where Ide (1935) described a new method of measuring Young's modulus by setting specimens vibrating using electrostatic traction.…”
Section: Introductionmentioning
confidence: 99%
“…Wood behaves like an elastic solid when force is applied to it, and therefore modulus of elasticity (MOE) is used to describe the stiffness of wood; in general a high value of MOE implies a high resistance of wood to deformation (Olaoye and Okon-Akan 2020). Scientists conventionally use universal testing machine (UTM) to determine elasticity of wood, and UTM tests are considered expensive, demanding high maintenance cost, and are destructive to samples (Amera et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of non-destructive acoustic methods (NDAT) is needed. There exist several non-destructive acoustic methods for estimating elasticity of wood based on ultrasound (Wang et al 2003), stress waves, infrared spectroscopy (Bailleres et al 2005), and vibration method (Barrett and Hong 2010;Almeida et al 2014;Guan et al 2019;Olaoye and Okon-Akan 2020). After analyzing anatomical, physical, and mechanical properties of plantation wood, this study considers four strains of clone plantation C. lanceolata timber in Kaihua County, Zhejiang Province as the research object.…”
Section: Introductionmentioning
confidence: 99%